PARAMETER GENETIK SEJUMLAH GENOTIP PADI DI LAHAN SAWAH BERPENGAIRAN TEKNIS DAN TADAH HUJAN [Genetic Parameters of Some Rice Genotypes Under Irrigated and Dryland Conditions] - Sutaryo, Bambang (BERITA BIOLOGI, 2014)
Development of high-yielding varieties depends on choice of parents, include per se performance, morphological and agronomic traits, and genetic diversity as determined through geographic origin. Indicators of success can be expected from the value of genetic progress and some other important genetic parameters. The purpose of this study was to calculate the genetic heterogenity, heritability and genetic advances of some quantitative characters of rice genotypes. Experiments were conducted in the district of Kulon Progo, namely: Wates and Panjatan (irrigated condition, dry season of 2012), in Giripeni (rainfed, medium altitude, wet season of 2012/2013), Samigaluh and Kalibawang (rainfed, high altitude, wet season of 2012/2013). Each experiment was designed using a randomized complete block with three replications.Data indicated that not all environmental conditions appropriate for the selection and development of genotype due to low value heritability and expectation genetic advances of each environment was lower than the value heritability and expectation genetic advances for the combined average of the environment. Wates was suitable location for grain yield selection and development in terms of the high heritability values. Kalibawang, Giripeni and Wates have considerable heritabilty value for 1000 grain weight character, hence they can be used as suitable selection locations for these characters.